Health tourism in Malaysia: the strength and weaknesses - I Aniza,; M Aidalina,; R Nirmalini,; MCH Inggit,; TE Ajeng, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Globalization has made health tourism possible and continues to flourish. For participating countries, this new industry rakes in billions of dollars a year, and is worth focusing on and being developed. Objective : This write up aims to find out the history and success of health tourism in countries around the world, study the scenario in Malaysia and propose strategies which could make Malaysia prosper with this multibillion dollar industry. Methodology : The methodology applied was compilation, data review and comparison from annual report, action plan report and articles. Result : In the ASEAN region, Malaysia is making a mark in the health tourism industry, thanks to the availability of medical and technical expertise, political and economical stability, high quality infrastructure, and scenic beauty of the land. Nonetheless, despite all these, Malaysia has yet to be at par with her neighbours- Thailand, Singapore and India, in terms of the number of foreign patients and the revenue gained from this industry. Thus there is a serious and urgent need to conduct research to analyze the current situation and future prospects of health tourism in Malaysia. This industry is open to all countries around the world. It is those countries that can continually analyze and adapt that will prosper in the emerging medical tourism industry. Some of the key issues which need to be addressed are those of promotion, finding the niche market, branding, legislations, immigration and quality of healthcare. In addition to these, matters regarding human resource, particularly that of internal brain-drain, need to be looked into. Conclusion : Malaysia has great potential of becoming the giant of the health tourism industry provided appropriate and timely actions are taken towards achieving it. The negative impact must not be ignored or overlooked; instead it must be thoroughly studied and rectified.